SIKAP UNGGAH-UNGGUH DAN SANTUN SEBAGAI CERMINAN PENGGUNAAN RAGAM BAHASA JAWA - Muhammad Sirojudin Kamal; Much Arsyad Fardani; Ahmad Bakhruddin (STKIP Subang, 2023)
This study aims to find out how the politeness and ungguh attitude of the 5th grade students of SD Negeri 3 Lebak is a reflection of the use of a variety of Javanese languages. This research was conducted at SD Negeri 3 Lebak, Pakis Aji sub-district, Jepara Regency. The subjects in this study were students and teachers of grade 5 SD Negeri 3 Lebak. This type of research is a case study qualitative research with data collection techniques using observation, interview, and documentation techniques. The results of the study showed that the polite and polite attitude of SD Negeri 3 Lebak students as a reflection of the use of the Javanese language variety was shown by students using good language when speaking, kissing hands or greeting the teacher, and smiling, greeting, and greeting the teacher. These three things are a form of polite and arrogant attitude of SD Negeri 3 Lebak students.